Reasons for Increased Social Distancing and Surface Disinfection from a Physics Perspective - Wen-Xin, Tang (Journal of Current Viruses and Treatment Methodologies, 2020)
This viewpoint uses physical principles to explain mechanisms behind social distancing and surface disinfection. It links particle dynamics and contact transfer to practical guidance and risk communication during respiratory epidemics.
Keywords: COVID- 19 preventive measures